PERCEPÇÃO DOS PAIS QUANTO AO TEMPO DE USO DE JOGOS DE VIDEOGAME ATIVO DE SEUS FILHOS: ESTUDO PRELIMINAR COMPARANDO O USO POR SEXO E GRUPOS DE IDADE - Francieli de Fátima Bento; Catiana Leila Possamai Romanzini (Universidade Estadual do Oeste do Paraná, 2014)
The aim of the study was to identify the perception of parents on the use time of active videogames by sex and age group. This is a descriptive cross-sectional study that included 120 parents and / or guardians of students aged 6-13 years enrolled in two private schools of the central region of Londrina. The average age of children was 9.3 ± 1.7 years. A self-administered questionnaire, adapted from the Active Gaming Questionnaire, was used to parents. Data were analyzed by SPSS 20.0, using frequencies, mean and standard deviation. The U Mann-Whitney and Fisher's exact tests were used with significance level of 5%. Students use active videogame 1-2 days a week and both on weekdays (95.8%) and during the weekend (88.3%), they use active video games for 2h/day. There was no association between sexes or age groups, both during the week (P = 0.059 vs P = 0.939), and during the weekend (P = 0.118 vs P = 0.924), respectively. There was no significant difference in the mean use time (minutes) of active videogames, or by sex or by age group, both during the week (P = 0.083 vs P = 0.610) and during the weekend (P = 0.086 vs. p = 0.506), respectively. The perception of parents regarding the use time of active videogames did not show significant differences between use time and sex and age group. Therefore, it could not be inferred that there is a different pattern of use of active videogames between boys and girls or that there are differences in the use time between younger and older adolescents.